Incidence and outcome of functional stroke mimics admitted to a hyperacute stroke unit. Issue 1 (28th August 2015) - Gargalas, Sergios; Weeks, Robert; Khan-Bourne, Najma; Shotbolt, Paul; Simblett, Sara; Ashraf, Leah; Doyle, Claire; Bancroft, Victoria; David, Anthony S
Abstract : Background: Some patients admitted to acute stroke units are diagnosed as stroke mimics. A minority have a functional neurological disorder ('functional mimics'). Aims: To determine the incidence of functional stroke mimics admitted to a hyperacute stroke unit (HASU); to compare their clinical characteristics with medical mimics and stroke cases and obtain information about outcomes. Methods: Patients admitted to the King's College Hospital HASU between 2011 and 2012 were analysed. Data were obtained from the Stroke Improvement National Audit Programme (SINAP) database. Expert consensus diagnosis was used to classify functional mimics. Follow-up information was obtained from a retrospective case series in primary care over the year following discharge. Results: 1165 patients were admitted to the HASU; 904 patients with stroke (77.6%), 163 medical mimics (14%) and 98 functional mimics (8.4%). Functional mimics were significantly more likely to be female (63.3%) versus 49.7% medical mimics and 45.5% stroke, and younger (mean age (SD)) 49.1 (18.8) than medical mimic (63.5 years (16.7)) and stroke cases (71 years (15.5)). Weakness and slurred speech were the commonest presentations of functional mimics and diagnostic MRI was used more often. Clinician recorded visual and speech symptoms and neglect were significantly more frequent in patients with stroke than either mimic group. Of the 68 functional mimics on whom follow-up information was obtained, 40 (59%) were referred to another service most often for a psychologically-based intervention. Conclusions: Functional stroke mimics are an important subgroup admitted to acute stroke services and have a distinct demographic and clinical profile. Their outcomes are poorly monitored. Services should be developed to better diagnose and manage these patients.